Severe Thalassemia Caused by Hb Zunyi [β147(HC3)Stop→Gln; HBB: c.442T>C)] on the β-Globin Gene. (2nd January 2019) - Su, Qiong; Chen, Shiping; Wu, Liusong; Tian, Runmei; Yang, Xiaoqin; Huang, Xiaoyan; Chen, Yan; Peng, Zhiyu; Chen, Jindong
Abstract: Hemoglobinopathies are caused by genetic defects on the globin genes. To date, more than 900 β-globin variants have been recorded worldwide. These gene alterations often cause either a decrease in β-globin synthesis or completely block synthesis, leading to a hemoglobinopathy. While most of these causative mutations are inherited, de novo mutations are quite rare. Here, we investigated three hemoglobinopathy cases. These patients developed severe hemolytic anemia at 3-5 months of age and were transfusion-dependent. In patient 1, a novel β variant, Hb Zunyi [β147(HC3)Stop→Gln; HBB : c.442T>C] was identified. This de novo mutation results in a stop codon substitution to a glutamine residue at codon 147 of the β-globin gene, and leads to severe thalassemia. In patient 2, we discovered the rare Hb Southampton mutation [β106(G8)Leu→Pro; HBB : c.320T>C], while in patient 3, the rare Hb Alesha mutation [β67(E11)Val→Met ( G TG> A TG); HBB : c.202G>A] was detected. The identification of the novel β variant, Hb Zunyi, has added to the human globin database and will shed light on future diagnosis of hemoglobinopathy/thalassemia and genetic counseling.